Análise de fatores geográficos e climáticos relacionados à distribuição de Phlebotominae (Diptera: Psychodidae) em área de transmissão de leishmaniose tegumentar americana no Estado do Espírito Santo, Brasil - Farias, Priscila Camargo Granadeiro (2014)
American cutaneous leishmaniasis (ACL) affects the skin and mucous membranes caused by dermotropic parasites of the genus Leishmania Ross, 1903. The parasites are transmitted through the bite of small insects of the family Psychodidae, the sandflies. The municipality of Cariacica, Espírito Santo, Brazil, has been in the last five years (2009-2013) among the five municipalities which had the largest numbers of reported cases in the, according to the State Department of Health (SESA-ES, 2014). The locality of Roda DÁgua has shown high epidemiological importance, due to the large concentration of cases contributing to the municipality notifications. Evaluating the registered cases from the region, from the medical reference service, Unidade de Medicina Tropical da Universidade Federal do Espírito Santo, it was observed that they occurred up to 550 m of altitude, in an area between 20-718 m above sea level. The most likely hypothesis is that the phenomenon is related to the vector distribution, since humans and animals are be present in all altitudes. From February 2002 to January 2004 sand flies were simultaneously captured in monthly collections in Roda D’Água , at three altitude levels: level 1 - up to 250 m, level 2 - between 250 and 500 m and level 3 - above 500 m. In each level, collection of sand flies was carried out in two environments: sylvatic and peridomicile. Collections were made using modified Shannon traps and by active search with Castro pooter. We evaluated flight activity of the species as the rainfall (rainy and dry seasons) and the seasonality. Only species known to be anthropophilic and with epidemiological importance were statistically analyzed. Abundance, richness, diversity, equitability, and dminance ecological indices were estimated. A total of 13,233 sand flies from 23 species were collected. The most abundant species was Nyssomyia intermedia (61.12%), followed by Pintomyia fischeri (18.20%) and Migonemyia migonei (8.68%), all species are anthropophilic. Pintomyia monticola represented 1.67% of the total specimens collected and is also antropophilic. The other species comprised 10.10% of the total specimens collected. The altitude affected the distribution of four species, and Ny. intermedia and Pi. fischeri were more abundant at level 2, Mg. migonei most abundant at level 1 and Pi. monticola at level 3. Nyssomyia intermedia and Mg. migonei were statistically more abundant in peridomestic areas and Pi. monticola in sylvatic environment. Pintomyia fischeri occurrence was not statistically significant according to environment, but it was the only one affected by the rain and showed seasonality, most commonly found in dry periods and during the winter. Nyssomyia intermedia seems to be the most important vector of ACL in Roda D’Água and Mg. migonei presents probably acting as asecondary vector. Pintomyia fischeri does not seem to be involved in disease transmission to humans in the locallity, despite having already been incriminated in others regions. According to its distribuition, probably Pi. monticola does not play a role in ACL transmission in Roda D’Água.